2022
DOI: 10.1186/s12906-021-03495-9
|View full text |Cite
|
Sign up to set email alerts
|

Euterpe oleracea fruit (Açai)-enriched diet suppresses the development of experimental cerebral malaria induced by Plasmodium berghei (ANKA) infection

Abstract: Background Cerebral malaria is one of the most severe complications attributed to protozoal infection by Plasmodium falciparum, gaining prominence in children mortality rates in endemic areas. This condition has a complex pathogenesis associated with behavioral, cognitive and motor sequels in humans and current antimalarial therapies have shown little effect in those aspects. Natural products with antioxidant and anti-inflammatory properties have become a valuable alternative therapeutic option… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 60 publications
1
5
0
Order By: Relevance
“…Additionally, mice treated with Art-AL combination treatment and Art-PT combination treatment showed a progressive significant improvement in survival rate, remaining alive until 13-days post-infection without evidence of neurological impairments. This study was consistent with a previous study that suggested that an increase in survival rate is usually related to neurological parameter improvement [ 66 , 67 ]. This could be related to the presence of bioactive compounds in the crude extracts, such as luteolin [ 59 ], vanillic acid [ 68 ], kaempferol [ 69 ], caffeic acid [ 57 ], gallic acid [ 60 ], and ellagic acid [ 70 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, mice treated with Art-AL combination treatment and Art-PT combination treatment showed a progressive significant improvement in survival rate, remaining alive until 13-days post-infection without evidence of neurological impairments. This study was consistent with a previous study that suggested that an increase in survival rate is usually related to neurological parameter improvement [ 66 , 67 ]. This could be related to the presence of bioactive compounds in the crude extracts, such as luteolin [ 59 ], vanillic acid [ 68 ], kaempferol [ 69 ], caffeic acid [ 57 ], gallic acid [ 60 ], and ellagic acid [ 70 ].…”
Section: Discussionsupporting
confidence: 93%
“…Phenolic compounds are excellent anti-oxidant owing to the presence of a hydroxyl group, which is available to capture oxygen free radicals. They can rebalance the production of oxygen species, which reduces cell damage caused by free radicals [ 67 ]. These results suggest that treatment with A. lancea , Prabchompoothaweep remedy, Art-AL, and Art-PT can provide anti-oxidant activity to the brain in the ECM.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the incomparable flavor, neuroprotective effects were already reported in different disease models, reinforcing the need to explore the potential effects of this fruit on health. In this context, our group is making major contributions to understanding the role of the EO-pulp diet on methylmercury intoxication and cerebral malaria, which are important health public problems in Brazil ( 3 , 13 ). We demonstrated that an EO-enriched diet prevented retinal oxidative and functional damage associated with methylmercury intoxication ( 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that an EO-enriched diet prevented retinal oxidative and functional damage associated with methylmercury intoxication ( 3 ). As well, this diet was able to reduce mortality, protect the blood–brain barrier, and reduce the neurocognitive effects of animals infected with Plasmodium berghei (ANKA) ( 13 ). Based on these studies, we decided to drive our focus to understanding the role of this diet in neurobehavioral changes, since they are emerging as a worldwide public health problem.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation